2011
DOI: 10.1371/journal.pone.0028638
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the Cell-Cycle Regulator RGC-32 in Epstein-Barr Virus-Immortalized Cells

Abstract: Epstein-Barr virus (EBV) is implicated in the pathogenesis of multiple human tumours of lymphoid and epithelial origin. The virus infects and immortalizes B cells establishing a persistent latent infection characterized by varying patterns of EBV latent gene expression (latency 0, I, II and III). The CDK1 activator, Response Gene to Complement-32 (RGC-32, C13ORF15), is overexpressed in colon, breast and ovarian cancer tissues and we have detected selective high-level RGC-32 protein expression in EBV-immortaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 74 publications
3
39
0
Order By: Relevance
“…Previous studies suggested that the oncogenic transcription factor c-Myc has a crucial role in cell growth, metabolism and proliferation [57], Cyclin dependent kinase 6 (CDK6) overexpression was implicated in the pathogenesis of B-cell malignancies [58], and also aberrant expression of the cell cycle regulatory protein Cyclin B1 has been detected in different lymphomas and EBV-immortalized cells [59], [60]. Earlier studies also demonstrated that these molecules are direct targets of IRF4 [44], [61].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggested that the oncogenic transcription factor c-Myc has a crucial role in cell growth, metabolism and proliferation [57], Cyclin dependent kinase 6 (CDK6) overexpression was implicated in the pathogenesis of B-cell malignancies [58], and also aberrant expression of the cell cycle regulatory protein Cyclin B1 has been detected in different lymphomas and EBV-immortalized cells [59], [60]. Earlier studies also demonstrated that these molecules are direct targets of IRF4 [44], [61].…”
Section: Resultsmentioning
confidence: 99%
“…EBV infection results in the deregulation of the cell-cycle, with EBNA 3C playing a key role in overriding G1/S, G2/M and mitotic checkpoints through numerous potential mechanisms that include transcriptional repression and the regulation of protein stability [83][84]. Disruption of the G2/M checkpoint may be mediated through effects on the Chk2 kinase and we have recently described upregulation of an activator of CDK1, RGC-32, in EBV-infected cells [69], [85]. Although Wee1 has not previously been implicated in EBV-mediated cell-cycle disruption, a recent microarray study identified WEE1 as the fourth most regulated gene in the ‘cell proliferation’ gene ontology category in newly EBV-infected hyperproliferating B-cells [86].…”
Section: Discussionmentioning
confidence: 99%
“…This protein forms complexes with cyclin-dependent kinase p34CDC2 to enhance kinase activity and induce Sphase entry and mitosis. 14,15 Moreover, RGC-32 promotes cell migration, inhibits angiogenesis and induces smooth muscle cell differentiation. [16][17][18][19] Interestingly, RGC-32 is abnormally expressed in the peripheral blood mononuclear cells of patients with hyper-immunoglobulin E syndrome and multiple sclerosis.…”
Section: Introductionmentioning
confidence: 99%